Periodontium and restoration: A comparative study of restored and unrestored molars - Adebola Oluyemisi Ehizele; Joan Emien Enabulele (Wolters Kluwer Medknow Publications, 2021)
Background: Restorations have been known to have a detrimental effect on the periodontium with certain teeth or groups of teeth prone to develop more severe periodontal destruction. This study compared the periodontal health of restored molars with that of unrestored molars and determined the correlation between the type, age, and status of the restorations on the molars and the health of the associated periodontium. Materials and Methods: Patients with at least one restored molar and its contralateral counterpart of one unrestored molar were recruited for the study. The type of restoration and material, age of restoration, and type of defects on the restoration were noted in the restored group, while the degree of tooth mobility, furcation involvement, gingival recession, gingival status, and periodontal pockets depth were measured in all teeth studied. Data were analyzed using IBM SPSS version 21.0. Results: A total of 160 molars (80 restored and 80 unrestored molars) were studied. There were more restored mandibular molars (53.7%) than restored maxillary molars (46.3%). More first molars (43) compared to second molars (37) were restored. The most prevalent type of restoration was amalgam restoration (67.5%), followed by glass ionomer cement restoration (10%). There was no statistically significant association between the type of restoration and the periodontal clinical parameters assessed (P > 0.05). Similarly, there was no statistically significant association between the class of the restoration whether Class I or II and the periodontal clinical parameters assessed. The restored molars had 3.2 (95% confidence interval [CI] 0.5-32.8) times the odds of bleeding on probing, 1.5 (95% CI 0.2-8.9) times the odds of having Grade 1 mobility, 2.1 (95% CI 0.5-10.0) times the odds of having Grade 1 gingival recession, and 1.5 (95% CI 0.3-9.2) times the odds of having Grade 1 furcation involvement than the unrestored. Conclusion: It can be concluded that there is no statistically significant difference in the health of the periodontium of restored and unrestored molars or correlation between the type, age, and status of the restorations on the molars and their periodontal health. The odds of having bleeding on probing, tooth mobility, gingival recession, and furcation involvement tends to be higher with the restoration of the molars.